Mediating effect of Commitment Continuance on Achievement Motivation and Task Performance - Adhie Fasha Nurhadian (LPPM STMIK Mardira Indonesia, 2023)
This study investigated the potential mediating role of commitment continuance in the relationship between achievement motivation and task performance. This study aims to examine the direct and indirect impacts of achievement motivation and task performance. The research methodology involved surveying 33 individuals currently employed in repair shops located within the city of Bandung. The researchers employed a survey instrument to gather employee data through direct distribution. The study's findings, which utilized structural equation modeling-PLS, suggest that a strong inclination towards achieving goals and a persistent sense of dedication is crucial in promoting employee excellence in job performance and maintaining allegiance to their respective employers. Furthermore, providing a conducive work environment, recognition, and assurance of job stability are crucial determinants in fostering elevated employee motivation and commitment levels. Therefore, organizations prioritizing and fostering these factors are more likely to attain exceptional performance results and favorable employee retention rates.